Performance of the XLIMUS Sirolimus‐Eluting Coronary Stent in Very Complex Lesions. (13th September 2016) - Briguori, Carlo; Visconti, Gabriella; Donahue, Michael; Di Palma, Vito; De Micco, Francesca; Signoriello, Giuseppe; Focaccio, Amelia
Abstract : Introduction: Stent delivery failure may occur especially when treating complex coronary artery stenosis. XLIMUS (CARDIONOVUM GmbH, Bonn, Germany) is a new sirolimus‐eluting stent (SES) with the following features: 1) cobalt chromium stent platform, with low (73 μm) strut thickness, (2) biodegradable polymer, and 3) potent antiproliferative drug (Sirolimus). Preliminary data suggest that XLIMUS SES may be ideal for the treatment of complex lesions. Methods: In this registry, we assessed the deliverability, safety, and efficacy of percutaneous coronary interventions (PCI) using the XLIMUS SES in patients undergoing elective PCI in native coronary vessels for complex de novo lesions, including severe calcification, severe tortuosity, and chronic total occlusion. The primary objective of the study is the delivery success of the XLIMUS SES. The secondary objective is the 1‐year rate of major adverse cardiac events (MACE; including all‐cause death, nonfatal myocardial infarction, and repeat revascularization). Results: A total of 200 consecutive patients with 255 lesions were included. Delivery success was obtained in 196 (98%) patients and in 251 (98.4%) lesions. The XLIMUS SES was successfully implanted on the first attempt with a single guidewire in 176 (88%) patients and in 208 (81.6%) lesions. Additional techniques to facilitate stent delivery (i.e., buddy wire, anchoring‐balloon, or GuideLiner catheter) were necessary in 47 (18.4%) lesions. Failure in XLIMUS SES implantation occurred in 4 (1.6%) lesions. MACE rate at 1 year was 9%. Conclusions: This registry supports the positive performance of the XLIMUS SES in the treatment of complex coronary artery lesions.